Silvopastoral projects in Colombia: Impacts on livestock productivity and deforestation - Buritica, Alexander; Ngaiwi, Mary; Gonzalez, Carolina; Castro, Augusto; Moreno, Manuel (2024)
Presented at the 2024 RIDGE December Forum – Workshop on Environmental Economics organized by the Central Bank of Chile, this study evaluates the impact of sustainable silvopastoral system (SPS) interventions in rural Colombia. Using a difference-in-differences approach, we find that treated producers show early signs of transitioning to sustainable practices, with increased paddock numbers and improved cattle weight, leading to higher income from livestock sales. However, no significant effects on milk productivity per cow were observed. At the rural property level, SPS interventions reduced deforestation, particularly after 2016, highlighting their environmental benefits. The presentation emphasizes the need for long-term monitoring and targeted incentives to ensure sustainable agricultural transitions and environmental preservation.